2010
DOI: 10.2903/j.efsa.2010.1723
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Geographic Distribution of Tick-borne Infections and their Vectors in Europe and the other Regions of the Mediterranean Basin

Abstract: This report is the second of a series of two technical assessments of the role of ticks in transmission of animal diseases and zoonoses in Eurasia. A previous published scientific opinion (EFSA Journal 2010; (8)8, 1703) focused on two diseases- Crimean-Congo haemorrhagic fever and African swine fever in Eurasia. The aim of this report is to provide an overview of the geographic distribution of tick species which have proven involvement in the transmission of pathogens causing animal diseases and zoonoses in Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 235 publications
1
5
0
Order By: Relevance
“…H. lusitanicum was the most prevalent tick species found in TBP-positive animals, which is consistent with previous reports carried out in wild ungulates in south-central Spain (Toledo et al, 2009;Ruiz-Fons et al, 2006). Ixodes ricinus is a highly prevalent tick species in most parts of central, western and northern Europe (EFSA, 2010), where it constitutes an important competent vector for the TBP tested (Battilani et al, 2017;Gray et al, 2019;Sprong et al, 2018). Nevertheless, Hyalomma spp.…”
Section: Ta B L Esupporting
confidence: 89%
“…H. lusitanicum was the most prevalent tick species found in TBP-positive animals, which is consistent with previous reports carried out in wild ungulates in south-central Spain (Toledo et al, 2009;Ruiz-Fons et al, 2006). Ixodes ricinus is a highly prevalent tick species in most parts of central, western and northern Europe (EFSA, 2010), where it constitutes an important competent vector for the TBP tested (Battilani et al, 2017;Gray et al, 2019;Sprong et al, 2018). Nevertheless, Hyalomma spp.…”
Section: Ta B L Esupporting
confidence: 89%
“…Moreover, Hyalomma ticks are not only expanding in their natural habitats but are also gradually extending into new environments, such as Central Europe [12,13]. There is also disturbing evidence of their adaption to new environmental niches [104]. It is therefore important to confirm whether the populations appearing in those new areas have become established.…”
Section: Habitats and Geographical Distributionmentioning
confidence: 99%
“…SFTS and JSF were dominant in Western Japan, whereas scrub typhus was dominant in Eastern and Western Japan. For scrub typhus and JSF, the pathogens were transmitted between vectors via gametes rather than through ticks sucking blood from an infected person or animal [ 47 ]. This suggested that the spread of the infection to an area is less likely to be affected by human mobility, and that the suspected region of infection corresponds to the vector’s habitat area.…”
Section: Discussionmentioning
confidence: 99%